Evolution of plastic deformation during multi-pass ECAP of an AA6060 aluminum alloy – An experimental flow line analysis - Nadja Berndt; Nadja A. Reiser; Martin F.-X. Wagner (Journal of Materials Research and Technology)
The deformation mode during ECAP is often idealized as simple shear, whereas experimental data and numerical simulations indicate the presence of a more complex deformation zone associated with strain gradients. As plastic flow is largely influenced by a material's processing history, especially in terms of grain size, texture and pre-deformation, the evolution of local material flow during multiple passes of ECAP is of significant interest. In this study, we use a method for visio-plastic analysis of the local deformation during ECAP of the aluminum alloy AA6060 via different processing routes in a friction-optimized tool with a tool angle of 90°: Prior to the final pass, the billets are cut lengthwise and prepared with a grid of indents on the inside. After interrupting the deformation during the final ECAP pass, both billet halves are extracted from the modular tool. The positions of the indents along several paths, i.e., flow lines, are analyzed from the partially deformed billets using optical images and a graphics software. For the analysis of the material flow we use a phenomenological model that describes the material path along the flow line based on a super-ellipse function, with only one parameter defining the evolution of curvature along the flow line. The resulting data allow for a detailed analysis of strain distributions and gradients inside billets after different numbers of passes. Through comprehensive microstructural and mechanical characterization of the processed material, we discuss changes in macroscopic properties and their relationship to microstructural evolution and local strain accumulation during ECAP.